Investigation of the function and behavior of p97/VCP - Khong, Zi Jia (2017)
p97/VCP is a multifunctional ATP-fueled ATPase quintessential for cell survival. As one of the most abundant cytosolic proteins, it is not surprising that p97/VCP regulates numerous pathways to ensure proper cell homeostasis. Here I show that p97/VCP regulates actin dynamics and cell migration via the ROCK pathway. The loss of p97/VCP triggers hyperphosphorylation of ROCK, resulting in extensive polymerization of actin. Persistent F-actin filaments and the absence of essential cell motility-related actin structures in p97/VCP knockdown cells led to compromised cell migration. I found that the loss of p97/VCP increases the level of ROCK-activating kinase, Plk1, through the ubiquitin-proteasome pathway. The increase in Plk1 thereafter affects the phosphorylation status of ROCK. Taken together, my study defines a hitherto unknown role of p97/VCP in actin regulation and describes a mechanism for the phosphorylation-dependent regulation of ROCK activity that implicates cancer metastasis and wound healing.